Conceptualization of the Three Centers of Education and Its Relevance to the National Education Political System - Saprianingsih, Sri Whenti; Sirozi, M (Journal of Educational Sciences, 2025)
The concept of three centers of education, introduced by Ki Hajar Dewantara, emphasizes that education is not only the responsibility of schools, but also involves families and communities as the main centers in shaping individual character and competence. These three elements have complementary roles and cannot be separated in a holistic education process. In the context of the Indonesian National Education System, the implementation of this concept has significant implications for the formulation of policies, curriculum development strategies, and pedagogical approaches that are oriented towards the needs of students as a whole. The synergy of these three centers is the key to the success of education that is able to form Indonesian people who are intellectually, emotionally, and spiritually intelligent. The national education system demands the integration of cross-sector policies, increased community participation, and strengthening the capacity of parents as primary educators. A collaborative approach is also needed between schools and the surrounding environment to create an inclusive and sustainable education ecosystem.